Recent Trends of Higher Education in India and Future Prospects - Mahapatra, Bhuban Chandra (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This study explores recent trends in higher education in India and examines future prospects within the framework of the National Education Policy 2020 (NEP-2020). Adopting a conceptual and policy analysis approach, the study synthesizes data from policy documents, government reports, and relevant literature to analyze key transformations in the sector. Higher education plays a critical role in shaping a knowledge-based society and driving national development; however, the Indian education system continues to face challenges related to access, equity, and quality. The paper adopts a conceptual and policy-based analysis to highlight key transformations, including the shift toward multidisciplinary learning, skill-based education, flexible curricula, and student-centered approaches. Emphasis is placed on the integration of Information and Communication Technology (ICT) as a crucial enabler for expanding access, enhancing teaching–learning processes, and improving institutional efficiency.           The findings indicate that NEP-2020 provides a comprehensive roadmap to reform higher education by promoting research, innovation, and global competitiveness. Initiatives such as digital learning platforms, open and distance education, and the establishment of regulatory bodies aim to strengthen governance and quality assurance. However, the effective implementation of these reforms remains contingent upon addressing critical barriers, including digital literacy gaps, teacher competency, infrastructure disparities, and socio-economic inequalities.          Furthermore, the study highlights the importance of continuous professional development for educators and the need for institutional readiness in adopting technological and pedagogical innovations. The future of higher education in India depends on the successful alignment of policy, practice, and stakeholder engagement. It is concluded that while NEP-2020 presents significant opportunities, its impact will largely depend on strategic implementation, adaptability, and sustained investment in the education sector to achieve inclusive and sustainable growth.